The role of unfractionated heparin for the antiaggregatory effect of aspirin in patients undergoing carotid endarterectomy: results of an observational clinical study - Brenner, Thorsten; Schmitt, Felix; Demirel, Serdar; Salgado, Eduardo; Celi de la Torre, Juan Antonio; Göring, Martin; Bruckner, Thomas; Böckler, Dittmar; Weigand, Markus A.; Hofer, Stefan; Attigah, Nicolas (Vascular, 2017)
The aims of the present study were to examine the influence of a low-dose unfractionated heparin regime on platelet aggregation and to additionally assess the prevalence of primary aspirin resistance in patients undergoing carotid endarterectomy. Therefore, 50 patients undergoing carotid endarterectomy were enrolled. A bolus of 3000 IU unfractionated heparin was administered 2 min before carotid cross-clamping additionally to standard antiaggregatory therapy. Haemostaseological point of care testing was performed twice, prior to surgery and 10 min after unfractionated heparin administration by the use of aggregometric and viscoelastic point of care testing. Following unfractionated heparin administration, the activated partial thromboplastin time increased significantly and clotting time in viscoelastic INTEM test was shown to be significantly prolonged. In contrast, the antiaggregatory effect of aspirin was not diminished in aggregometric ASPI test. A low-dose unfractionated heparin regime during carotid endarterectomy was therefore considered to be safe, without diminishing the antiplatelet effect of aspirin. Moreover, aggregometric point of care testing was identified to be a suitable tool for the identification of patients with primary aspirin resistance (n = 3).
First published: March 17, 2016
Gesehen am 09.07.2018